Synthesis of model terpene-derived copolymers in supercritical carbon dioxide for cosmetic applications. (15th August 2021) - Bennett, Thomas M.; Portal, Julien; Jeanne-Rose, Valérie; Taupin, Simon; Ilchev, Alexander; Irvine, Derek J.; Howdle, Steven M.
Graphical abstract: Abstract: There is currently a strong drive within the cosmetics industry to replace petroleum based solvents and polymers with renewable alternatives. Copolymers of 2-ethylhexyl acrylate (2EHA) and maleic anhydride (MA) are interesting model candidates to be used in make-up and skincare applications as cross-linkable film forming materials, but are currently synthesised in organic solvents and are derived from petroleum. Herein, we have studied and optimised the copolymerisation of these two monomers in supercritical carbon dioxide (scCO2 ). The kinetics of the reaction and resulting products were compared with analogues synthesised in a 30/70 solvent mixture of ethyl acetate/isododecane (EtOAc/IDD), which mimics current industry practices. Initially, the incompatibility of these two monomers in the absence of a solvent lead to mixed homo- and copolymer products during reactor pressurisation. This was overcome by devising a new synthesis approach, in which MA is first dissolved in scCO2 at high temperature, followed by the addition of 2EHA and a radical initiator in situ via a HPLC pump. Copolymers synthesised using this new methodology were added to simple cosmetic formulations and evaluated for their resistance to olive oil, where they performed comparably with those synthesised in EtOAc/IDD. The renewable content of the reaction was then increased further, by substituting the monomer 2EHA with the terpene-derived alternatives isobornyl acrylate and α-pinene acrylate. This study is an important step towards materials that can achieve outstanding levels of performance in a variety of cosmetic applications, and are also more in phase with green chemistry criteria.